PEMBELAJARAN ORANG DEWASA BERBASIS ANDRAGOGI: TINJAUAN TEORI - Sumiyarno Sumiyarno (Jurnal Ilmiah Visi, 2007)
The education level of many adult people generally is low. The result of examining towards a considerable body of literature on the concepts of andragogy shows that now many of practices of adult education and training have been conducted by using a pedagogical approach. Their practices are not effective since the orientation toward learning for adult people is one of subject-centeredness. Consequently, the education and training for adults should be promoted by using andragogybased learning and the orientation toward learning is one of problem-centeredness.